Sitio web de grupos de investigación de la ESPAM MFL - Moreira Andrade, Karelys Juletzy (2025)
This research focuses on the development of a website for the Research Groups of ESPAM MFL, aiming to enhance communication and increase the visibility of researchers’ activities. Using the Extreme Programming (XP) methodology, an iterative and collaborative process was carried out, enabling the creation of a dynamic and functional website. During the planning phase, the website objectives were outlined, and the necessary functionalities were defined to meet client requirements. In the design phase, wireframes were created, and the information architecture was developed. Coding was carried out through short and frequent iterations, prioritizing functionality and code simplicity. Testing was performed continuously throughout the development process, ensuring the quality and stability of the website. Finally, after completing the development iterations and implementing the necessary corrections, the website was officially launched and made available for use by the ESPAM MFL research community. The final result is a website featuring user profiles, news publications, events, and research projects, as well as internal and external communication tools, which facilitate collaboration among researchers, promote the dissemination of generated knowledge, and strengthen ESPAM MFL’s institutional image as a research reference center.